EFEKTIVITAS PELATIHAN PEMBUATAN KONTEN DIGITAL DALAM MENINGKATKAN PEMASARAN PRODUK KELOMPOK WANITA TANI (KWT) PANCASONA - Solecha, Kusmayanti; Irnawati, Oky; Indriyani, Furi; Rachmi, Hilda; Tanjung, Handra Putratama; Hidayat, Nasrul Walid (Jurnal AbdiMas Nusa Mandiri, 2024)
The Women Farmers Group (KWT) Pancasona, located in the Dephan Pondok Rajeg Asri complex, manages 5 plot areas and 1 greenhouse, focusing on providing organic vegetables. However, they face challenges in effectively utilizing social media to promote their harvests and sales, particularly in digital content creation. This community service initiative aims to provide training in digital content creation using the Canva application to enhance product marketing through social media. The methods used include observation to identify the problems faced by the partners, preparation of appropriate training materials, conducting training and mentoring in technology-based content creation with Canva, and evaluation to measure participants' understanding after the training. The results show that participants' understanding of the Canva application increased from 61% in the pretest to 92% in the posttest. Feedback from questionnaires indicated high satisfaction with the materials, facilities, and benefits of the training. Overall, this activity was effective in improving the knowledge and skills of participants, helping to provide solutions to marketing problems by optimizing social media use.